Pengetahuan, Sikap dan Tindakan Masyarakat tentang Kebijakan Pemerintah dalam Upaya Pengendalian Corona Virus Disease 2019 - Vania Sartika Putri Lahinda; Oksfriani Jufri Sumampouw; Novie Homenta Rampengan (Universitas Sam Ratulangi, 2021)
Background: Corona Virus Disease 2019 (Covid-19) has become a worldwide pandemic. Covid-19 is still a public health problem, especially in Indonesia. One of the problems to faced in controlling Covid-19 is community knowledge, attitudes and action. The purpose of this study is to description knowledge, attitudes and action on public actions regarding government policies in an effort to control Covid-19 in the city of Manado. Method: This is an observational study with a cross-sectional approach. The research was carried out in the Manado city in September 2020 - February 2021. The respondents in this study were residents of the Manado city who met the inclusion criteria. This study used 385 respondents. The research variables are knowledge, attitudes and actions. Informants were obtained using an online questionnaire using the google form application. Data analyzed univariatly. Results: The results showed that the most respondents are 17-25 years old (69.1%), female (66.2%), have college education (74.8%) and work as students (36.9%). Furthermore, most of the respondents fall into the very good category for knowledge (88.3%), attitude (67.0%) and action (54.8%). Conclusion: That can be conclude the people of the city of Manado have excellent knowledge, attitudes and actions about control policies of Covid-19. Therefore, it is necessary to continuously disseminate information about efforts to control and prevent Covid-19.